Analisis Peramalan Impor Beras Indonesia - Deby Ramadanthy; Achmad Tjahja Nugraha; Agustina Senjayani (Sharia Agribusiness Journal, 2022)
The cause of the heavy flow of rice imports due to differences in domestic prices and international rice prices cannot be separated from problems with the rice production system and distribution or domestic rice trading system. The objectives of this study are (1) to determine the characteristics of the country of origin of Indonesian rice imports, (2) to obtain a data forecasting model for the volume of Indonesian rice imports using the Box-Jenkins ARIMA method in 2025, and (3) to analyze the forecasting of the value of Indonesian rice imports in 2025 using the ARIMA Box-Jenkins method. ARIMA Box-Jenkins.Data collection on the volume of rice imports and the value of rice imports from January 2010 to December 2019. The data analysis method uses the ARIMA model time series with the help of Software Eviews 10. The results of data processing show that the MA model (1) is the best model. Which is used for forecasting the volume of rice imports is Zt = 703374.4 + 0.157003 + et, where the forecasting results state that the volume of rice imports has increased. Furthermore, the results of data processing on the value of the volume of rice imports show that the MA model (1) is the best model with a general form, namely Zt= 283002.2 + 0.132568 + et. Results of data processing on the value of rice imports indicate an increase in prices in units of US$. Forecasting the volume of Indonesian rice imports and Indonesian rice imports will increase during 2025. Keywords: Import, Rice, Indonesia, Box-Jenkins, Eviews Abstrak:Penyebab arus derasnya impor beras karena perbedaan harga dalam negeri dan harga beras internasional tidak dapat dipisahkan dari persoalan sistem produksi beras dan distribusi atau tata niaga beras domestik. Tujuan penelitian ini adalah (1) mengetahui karakteristik negara asal impor beras Indonesia, (2) mendapatkan model peramalan data volume impor beras Indonesia menggunakan metode ARIMA Box-Jenkins pada tahun 2025, dan (3) menganalisis peramalan nilai impor beras Indonesia tahun 2025 menggunakan metode ARIMA Box-Jenkins.Pengambilan data volume impor beras dan nilai impor beras terhitung dari bulan Januari 2010 hingga Desember 2019. Metode analisis data menggunakan rentang waktu (time series) model ARIMA dengan bantuan Software Eviews 10. Hasil pengolahan data menunjukkan bahwa model MA (1) merupakan model yang terbaik yang dijadikan untuk peramalan pada volume impor beras sebesar Zt = 703374,4 + 0,157003 + et, dimana hasil peramalan menyatakan bahwa volume impor beras mengalami peningkatan. Selanjutnya, hasil pengolahan data pada nilai volume impor beras menunjukkan bahwa model MA (1) merupakan model terbaik dengan bentuk umum yaitu Zt = 283002,2 + 0,132568 + et. hasil dari pengolahan data pada nilai impor beras menyatakan adanya peningkatan harga dengan satuan US$. Peramalan volume impor beras Indonesia dan nila impor beras Indonesia akan mengalami peningkatan selama tahun 2025. Kata Kunci: Impor, Beras, Indonesia, Box-Jenkins, Eviews